ChemInform Abstract: Synthesis of α‐Alkylated β‐Ketoesters by Alkoxycarbonylation/Michael Addition Domino Reaction. Issue 26 (6th June 2013) - Wahl, Benoit; Philipson, Yann; Bonin, Helene; Mortreux, Andre; Sauthier, Mathieu
Abstract Highly functionalized α‐alkylated β‐ketoesters are prepared in a novel two‐step one‐pot domino alkoxycarbonylation and Michael addition reactions.